„Ten człowiek potrafi siebie obrzydzić wszystkim, którzy chcieliby mu pomóc” O korespondencji Jerzego Giedroycia i Teodora Parnickiego [rec. Jerzy Giedroyc, Teodor Parnicki: Listy 1946–1968. Oprac., wstępem i przypisami opatrzył Andrzej Dobrowolski. Cz. 1 - Gorliński-Kucik, Piotr (Śląskie Studia Polonistyczne, 2015)
The author analyses Andrzej Dobrowolski’s exquisite edition of letters of the editor of Kultura Jerzy Giedroyc and Teodor Parnicki written between 1946 and 1968. This volume of their prolific correspondence reveals a lot of previously unknown facts from the biography of the author of Słowo i ciało and the life of immigrants at the time of the Polish People’s Republic, and shows problems Parnicki had publishing his novels in the Instytut Wydawniczy PAX.